POST DISASTRACE DAYAH MANAGEMENT: RECONSTRUCTION OF A LEADERSHIP MODEL IN RESILIENCE BASED ISLAMIC EDUCATION IN ACEH - Suzanni (TADBIRUNA: Jurnal Manajemen Pendidikan Islam, 2026)
This research is motivated by the existential challenges faced by Islamic boarding schools (dayah) in Aceh post-disaster, where the 2004 tsunami and subsequent disasters like flash floods and landslides not only destroyed physical infrastructure but also shook the foundations of traditional dayah leadership that has long relied solely on spiritual authority. Dayah are required to transform into emergency response institutions and community recovery centers, yet a contextual disaster management and leadership model aligned with Islamic educational values has not been systematically formulated. This study aims to reconstruct a resilience-based dayah leadership model through critical synthesis of current literature. The research methodology employed is a literature review using a qualitative approach, drawing from books, international and national scholarly journal articles, and research reports. Data validity was tested through source triangulation, meticulous observation, and audit trails. The research findings reveal four main points: first, the transformation of the role of dayah leaders from spiritual authorities to crisis agents that broaden the scope of leadership; second, adaptive strategies in physical reconstruction and curriculum through participatory models and the integration of disaster values into the traditional Islamic curriculum; third, the internalization of resilience values such as patience, reliance on God, and communal cooperation through a 24-hour dayah education system; fourth, an organic collaborative network model between dayah, the government, and civil society that balances self-reliance and partnership. The study concludes that dayah resilience is not merely about survival but growing into a stronger and more relevant version. Implementation of the research findings includes integrating disaster training in cleric development, developing yellow-book-based mitigation modules, institutionalizing regular collaboration forums, and mapping alumni networks as emergency response hubs